Optimizing land acquisition information system utilization using TAM in Kantor Pertanahan Kota Bandung - Ridmadhani, Raden Shafira Annisa; Gunawan, Syam; Supriana, Fadhlanrashif Ibrahim (Jurnal Abmas, 2026)
The implementation of the Sistem Informasi Pengadaan Tanah (SIPT) is a strategic effort to ensure the effectiveness, transparency, and accountability of land acquisition within government agencies. However, in practice, the effectiveness of this system is highly dependent on the readiness and acceptance of its users in the field. This activity aims to optimize the use of SIPT at Kantor Pertanahan Kota Bandung using the Technology Acceptance Model (TAM). The implementation is conducted through a participatory and evaluative approach with the Tim Pelaksana Pengadaan Tanah di Kantor Pertanahan Kota Bandung, comprising 30 participants. The process includes identifying initial conditions, mentoring and strengthening, and evaluation using a questionnaire. Data are evaluated systematically in Jamovi to assess the extent of user perceptions and the actual ease of use of SIPT. The results show that all TAM variables have a positive and significant effect on actual system use. Perceived usefulness and ease of use have been shown to play an important role in shaping user attitudes and intentions. These findings emphasize the importance of improving system quality and operational ease to optimize the sustainable use of SIPT.
Keywords: SIPT; sistem informasi pengadaan tanah; TAM; technology acceptance model; user acceptance